1999
DOI: 10.3354/ame017145
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide-resistant respiration in diverse marine phytoplankton. Evidence for the widespread occurrence of the alternative oxidase

Abstract: In higher plants, the alternative oxidase (AOX) is the terminal oxidase in a mitochondrial electron transport chain thought to allow carbon flow through glycolysis and the citric acid cycle when cellular energy levels are high. In phytoplankton, information is lacking on the taxonomic distribution and metabolic properties of the AOX. We used cyanide-resistant respiration to indicate the presence of the AOX, and the AOX inhibitors, salicylhydroxamic acid (SHAM) and propyl gallate (PG), to estimate the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A slope <1 would indicate a decline in O 2 uptake with increasing irradiance and a slope >1 would indicate an increase in O 2 uptake with increasing irradiance. Only 3 of the species (Prorocentrum minimum, Pycnococcus provasolii and Storeatula major) had slopes that were 20 to 30% >1, indicating light-stimulated O 2 uptake, which is consistent with other species from the same taxonomic groups (25 to 35%: Lewitus & Kana 1995, Eriksen & Lewitus 199935 to 50%: Suggett et al 2008). Curiously, we did not observe any light-stimulated O 2 uptake for Thalassiosira weissfloggi and Dunaliella tertiolecta, as might have been expected given previous studies of green algae and diatoms (Weger et al 1988, Luz et al 2002.…”
Section: Reductant Flow O 2 Consuming Pathways and Pqsupporting
confidence: 66%
See 1 more Smart Citation
“…A slope <1 would indicate a decline in O 2 uptake with increasing irradiance and a slope >1 would indicate an increase in O 2 uptake with increasing irradiance. Only 3 of the species (Prorocentrum minimum, Pycnococcus provasolii and Storeatula major) had slopes that were 20 to 30% >1, indicating light-stimulated O 2 uptake, which is consistent with other species from the same taxonomic groups (25 to 35%: Lewitus & Kana 1995, Eriksen & Lewitus 199935 to 50%: Suggett et al 2008). Curiously, we did not observe any light-stimulated O 2 uptake for Thalassiosira weissfloggi and Dunaliella tertiolecta, as might have been expected given previous studies of green algae and diatoms (Weger et al 1988, Luz et al 2002.…”
Section: Reductant Flow O 2 Consuming Pathways and Pqsupporting
confidence: 66%
“…Generally, however, the effect of light on O 2 uptake over the range from dim irradiance to saturating irradiance for photosynthesis may range from close to nil to highly stimulatory, particularly at light-saturated photosynthesis. Indeed, it is common to observe O 2 uptake rates as high as 30 to 40% of the gross O 2 evolution rate in cultivated algae under saturating light (Weger et al 1988, Lewitus & Kana 1995, Eriksen & Lewitus 1999, Suggett et al 2008, which means that 30 to 40% of photosynthetic reductant is directed to O 2 reduction rather than to anabolism.…”
Section: Reductant Flow O 2 Consuming Pathways and Pqmentioning
confidence: 99%
“…Interestingly, in both phytoplankton (Weger and Dasgupta, 1993;Eriksen and Lewitus, 1999) and higher plants (Vanlerberghe and Ordog, 2002), AOX can be strongly induced by nutrient limitation and may thus play an important role in such environments.…”
Section: Aox Respiration In Marine Bacteriamentioning
confidence: 99%
“…Studies which have been done suggest that AOX may indeed be widespread in aquatic environments. For example, a significant capacity for AOX respiration (i.e., O 2 uptake resistant to CN but sensitive to AOX inhibitors) has been found in members of the Euglenophyceae, Chlorophyceae, Rhodophyceae, Bacillariophyceae, Cryptophyceae, Chrysophyceae and Dinophyceae (Benichou et al, 1988;Weger and Dasgupta, 1993;Robaina et al, 1995;Eriksen and Lewitus, 1999). Also, isotope discrimination experiments (which use the difference in isotopic discrimination against 18 O by cyt oxidase and AOX to estimate the partitioning of electrons in respiration) in Lake Kinneret suggest a largescale uptake of O 2 by AOX in this environment (Luz et al, 2002).…”
Section: Aox Respiration In Marine Bacteriamentioning
confidence: 99%
“…Recently, it has been shown that AOX is widespread and quantitatively important among diverse aquatic phytoplank-ton and can be stimulated by various environmental factors (McIntosh et al 1998;Eriksen and Lewitus 1999). In particular, Maxwell et al (1999) demonstrated the engagement of this mechanism as a response to the formation of reactive oxygen species that resulted in oxidative stress.…”
Section: Evaluation Of the Significance Of O 2 Uptake Mechanisms-mentioning
confidence: 99%